The development of hologram design as the information delivery to Kinabalu National Park visitors / Brandon Caine Mail @ Firid - Mail @ Firid, Brandon Caine (2018)
This study discusses the development of Information Delivery based on The Mythical Story of Gayo Nakan. Information delivery has many type to interpret on. There are like Information delivery about something that want to promote or deliver. Information delivery also can make people aware about something such as The Mythical Story of Gayo Nakan that mythical story from Mount Kinabalu. The concept will be use is a ―movie trailer based on The Mythical Story of Gayo Nakan. As we know The Mythical Story of Gayo Nakan nowadays still been not kown among young people especially Malaysian people so this platform will encourage these people to think about The Mythical Story of Gayo Nakan. Beside that, this research is also to finding information delivery design using video content like movie trailer as a information delivery to introduce The Mythical Story of Gayo Nakan. This research is using quantitative method which is measuring data using question such as survey in specific people and specific area.